High intensity surface plasma waves, theory and PIC simulations. (31st October 2017) - Raynaud, M; Héron, A; Adam, J-C
Abstract: With the development of intense (>10 19 W cm −2 ) short pulses (≤25 fs) laser with very high contrast, surface plasma wave (SPW) can be explored in the relativistic regime. As the SPW propagates with a phase velocity close to the speed of light it may results in a strong acceleration of electron bunches along the surface permitting them to reach relativistic energies. This may be important e.g. for applications in the field of plasma-based accelerators. We investigate in this work the excitation of SPWs on grating preformed over-dense plasmas for laser intensities ranging from 10 19 up to 10 21 W cm −2 . We discuss the nature of the interaction with respect to the solid case in which surface plasmon can be resonantly excited with weak laser intensity. In particular, we show the importance of the pulse duration and focalization of the laser beam on the amplitude of the SPW.